Thermo-enzymatic hydrolysis of bitter cassava starch: Fundamental and process optimization studies - Noorulnajwa Diyana, Yaacob
Fundamental characterization of cassava starch that will be used in bioethanol production was studied entensively. In the present study, non edible cassava (Manihot esculenta) is used as the raw material for starch, which undergoes enzymatic hydrolysis to produce glucose then precede the fermentation to obtain bioethanol. Proximate analysis of this starch showed that the carbohydrate content is 91.17% while apparent and total amylose are 16.6% and17.1% respectively. Phosphorus and ash showed the lowest value and the moisture content is 10.5%. Nitrogen and Total fat are negligible. By using various analytical equipments, its characteristics were identified. It was found that the root starch has a polyhedric shape by visualizing under SEM and the surface was smooth with no evidence of pores. Under XRD, the pattern shows that the cassava was classified as A-type starch and their gelatinization temperature was high, 89.4°C. Swelling and solubility take place as a result of gelatinization of starch granule. All the fundamental characteristics, gave a good impact for this starch to be used as a raw material in bioethanol industry. Enzymatic hydrolysis of starch from natural sources finds potential application in commercial production of bioethanol. The effects of various process variables were studied for optimum conversion of cassava starch to glucose using α-amylase and amyloglucosidase. Starch is a reserved polysaccharide of plant origin, which cannot be converted to sugar easily. Starch saccharification requires prior gelatinization by heat treatment, liquefaction by α- amylase and conversion to sugars by amyloglucosidase. In order to get higher glucose concentration; liquefaction and saccharification processes must be optimized. Full factorial composite experimental design and central composite design (CCD) were used in the design of experiments and analysis of results. Preliminary study was done to investigate the potential variable for these two processes. The performance of α- amylase in liquefaction was determined by dextrinizing activity (D.A.) while the performance of amyloglucosidase was based on glucose concentration. The optimal condition for liquefaction for 35% cassava starch slurry was obtained by using 0.33% BAN480L in sodium acetate buffer (pH 7) at 85°C for 12.72 min. The optimal conditions for sacharification were found to be at 60.75°C, pH 4.53, using 0.2% AMG300L in 40 min. A model adequacy was very satisfactory, as coefficient of determination were 0.9977 and 0.9795 for liquefaction and sacharification, respectively.